The Role of Stakeholders in Preventing and Eradicating Land Mafia in Indonesia - Supadno Supadno; Nur Wening (PT. Hafasy Dwi Nawasena, 2026)
This study aims to analyze the role of stakeholders in the prevention and eradication of land mafia practices in Indonesia using a Systematic Literature Review (SLR) approach. Land mafia is an organized crime in the land sector involving multiple actors and causing serious impacts on legal certainty, economic losses, and social conflicts within society. This research employs a qualitative method based on library research by analyzing relevant scientific articles, journals, and policy documents. The findings indicate that land mafia practices are carried out through various modus operandi, including document forgery, issuance of multiple land certificates, illegal land occupation, and collusion with public officials. Government efforts to prevent and eradicate land mafia include the establishment of the Anti-Land Mafia Task Force, digitalization of land services, implementation of electronic land certificates, and the Complete Systematic Land Registration (PTSL) program. In addition, the involvement of the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency, law enforcement agencies, local governments, supervisory institutions, society, and the private sector plays a crucial role in the effectiveness of land mafia eradication efforts. This study also identifies several challenges, such as weak inter-stakeholder coordination, limited integration of land administration data, and low legal literacy among the public. Based on stakeholder theory proposed by R. Edward Freeman, the success of land mafia prevention and eradication depends on the synergy among all parties involved